PEMANFAATAN CENDAWAN ENTOMOPATOGEN Beauveria bassiana (BALSAMO) VUILEMIN DALAM PENGENDALIAN HAMA TANAMAN - Puu, Yustina Maria Silvia Wonga (AGRICA, 2009)
The using of synthetic pesticide in control of crop pest cause various of negative impacts like resistance, resurgence, the incidence of secondary pets, killing of the natural enemy and is impure of environmental even death to human being and animal. One of the correct operation alternative to decrease the using of synthetic pesticide is biological control with exploiting of entomopathogen caiied Beauveria bassiana. This Entomopatogen has an ability for infection of insect either through direct contact, and also inoculation of woof was given to target insect by producing the toxin so that insect body closed conidia and become hard like a mummy. The ability is also influenced by the condition of environment especially temperature and dampness. B. bassiana has high patogenistas ability almost in all of the insect. B.bassiana can depress the population of coffee powder H. hampei of Helopeltis spp equal to 76% and the other insect type. Application of B. bassiana don't generate death at another pest which good for (natural enemy) in nature. Infection mushroom mechanism of entomopathogenic B. bassiana in control of pest in the field happened by direct contact, inoculation and also contamination with target pest insect and effective in controlling of various pest insect type. Its effectiveness is influenced by a variety of isolate types, the closeness of spore, quality of media grow, controlled pest type, age of stadia pest, application time, application frequency and environmental factor.